Social-Economic Transformation in Traditional Cultural Festivals: A Study on the Isen Mulang Cultural Festival - I Wayan Salendra; Akhmad Jaki; Depita Kori; Eka Naralatih; Eka Susilawati; Febriana Resti Novi Afianty (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
Cultural festivals play a vital role in promoting tourism and preserving heritage, but their sustainability and broader socio-economic impacts are not always well understood. This research aims to investigate the perceptions of stakeholders and tourists regarding the Isen Mulang Cultural Festival in Central Kalimantan, Indonesia, to assess its demand and supply aspects and its potential for cultural and economic development. Qualitative in-depth interviews were conducted with five stakeholders involved in the tourism sector, and their responses were content-analyzed and organized into a SWOT matrix. The study revealed the importance of enhancing security measures, providing additional accommodation options, and investing in festival promotion to attract more tourists and boost socio-economic benefits. The Isen Mulang Cultural Festival has the potential to contribute significantly to cultural and economic development in Central Kalimantan. However, addressing identified shortcomings and increasing government involvement are crucial steps to ensure its sustainable growth and appeal to international tourists.